Adult Onset Still’s Disease: A Case Report with a Rare Clinical Manifestation and Pathophysiological Correlations - Katerina M. Antoniou; George A. Margaritopoulos; Ioannis Giannarakis; Christianna Choulaki; Nikos Fountoulakis; Nikos M. Siafakas; Prodromos Sidiropoulos (Case Reports in Medicine)
Adult-onset Still’s disease is an inflammatory multisystemic disease of unknown etiology. Pleuritis is the most common pulmonary manifestation and pleural effusions are usually exudates with a predominance of neutrophils. We report a case of an eosinophilic pleural effusion as a novel and hitherto unrecognized manifestation of active adult-onset Still’s disease. We also observed a marked NLRP3 inflammasome activation with increased production of IL-1β which coincided with the development and resolved upon remission of the pleural effusion suggesting a possible novel pathogenetic pathway for the development of pleural effusions in the context of the auto-inflammatory disorders.